Primates, Lice and Bacteria: Speciation and Genome Evolution in the Symbionts of Hominid Lice. (14th April 2017) - Boyd, Bret M.; Allen, Julie M.; Nguyen, Nam-Phuong; Vachaspati, Pranjal; Quicksall, Zachary S.; Warnow, Tandy; Mugisha, Lawrence; Johnson, Kevin P.; Reed, David L.
Abstract: Insects with restricted diets rely on symbiotic bacteria to provide essential metabolites missing in their diet. The blood-sucking lice are obligate, host-specific parasites of mammals and are themselves host to symbiotic bacteria. In human lice, these bacterial symbionts supply the lice with B-vitamins. Here, we sequenced the genomes of symbiotic and heritable bacterial of human, chimpanzee, gorilla, and monkey lice and used phylogenomics to investigate their evolutionary relationships. We find that these symbionts have a phylogenetic history reflecting the louse phylogeny, a finding contrary to previous reports of symbiont replacement. Examination of the highly reduced symbiont genomes (0.53–0.57 Mb) reveals much of the genomes are dedicated to vitamin synthesis. This is unchanged in the smallest symbiont genome and one that appears to have been reorganized. Specifically, symbionts from human lice, chimpanzee lice, and gorilla lice carry a small plasmid that encodes synthesis of vitamin B5, a vitamin critical to the bacteria-louse symbiosis. This plasmid is absent in an old world monkey louse symbiont, where this pathway is on its primary chromosome. This suggests the unique genomic configuration brought about by the plasmid is not essential for symbiosis, but once obtained, it has persisted for up to 25 My. We also find evidence that human, chimpanzee, and gorilla louse endosymbionts have lost a pathway for synthesis of vitamin B1, whereas the monkey louse symbiont has retained this pathway. It is unclear whether these changes are adaptive, but they may point to evolutionary responses of louse symbionts to shifts in primate biology.